Evaluation of the Labour Market Situation of Young People in EU Countries – The Multiple Regression Approach - Kawecka, Magdalena (Ocena sytuacji młodych ludzi na rynku pracy w krajach Unii Europejskiej – podejście regresji wielorakiej, 2023)
The article considers the problems of young people aged 20-24 on the labour market affected by unemployment in European Union countries. Unemployment is one of the most important economic and social problems, which at the same time constitutes one of the biggest measures characterising the condition of the economy. The diversity of the economic situation in EU countries directly affects young people, an individual group of people entering the labour market and have little or no professional experience. At the same time, they are ready to start work, facing great difficulties in entering the market, influenced by socio-economic as well as demographic factors which directly and indirectly affect employment. Considering the above premise, the aim of the article was to identify the determinants of unemployment of young people aged 20-24 in the EU. The study used data from two years: 2010 and 2020, and applied multiple regression. Statistical data were taken from Eurostat databases. The study allowed to examine the dependence of the influence of individual socioeconomic as well as demographic factors on youth unemployment. The study found that the multivariate regression showed that factors related to young people's participation in education and training (including the NEET rate) relative to labour market status, as well as social inclusion, had a significant impact on the unemployment studied. Over the decade, a decrease was seen in unemployment in most EU member states, in as many as 19 countries, while the remaining eight countries showed an increase.
Econometrics = Ekonometria, 2023, Vol. 27, No. 3, s. 35-58
Keywords: labour market; European Union; young people; unemployment; multiple regression; rynek pracy; Unia Europejska; młodzi ludzie; bezrobocie; regresja wieloraka